2017
DOI: 10.1002/adsc.201601262
|View full text |Cite
|
Sign up to set email alerts
|

Green Organocatalytic Synthesis of Indolines and Pyrrolidines from Alkenes

Abstract: Employing a green and efficient 2,2,2‐trifluoroacetophenone‐catalyzed oxidation of alkenes, which utilizes H2O2 as the green oxidant, a novel and sustainable synthesis of indolines and pyrrolidines was developed. This constitutes a cheap, general and environmentally‐friendly protocol for the synthesis of substituted nitrogen‐containing heterocycles. A variety of substitution patterns, both aromatic and aliphatic moieties, are well tolerated leading to the desired nitrogen heterocycles in good to excellent yiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 49 publications
0
41
0
Order By: Relevance
“…Utilizing o ‐allylanilines and phenols as starting materials, a variety of indolines, pyrrolidines, and dihydrobenzofurans can be synthesized. In the first step, the olefinic group is epoxidized, and subsequently, the functional group attacks the ring and opens the epoxide to afford the desired cyclized product, with or without the use of a suitable additive (Schemes and ).…”
Section: 22‐trifluoroacetophenonementioning
confidence: 99%
See 1 more Smart Citation
“…Utilizing o ‐allylanilines and phenols as starting materials, a variety of indolines, pyrrolidines, and dihydrobenzofurans can be synthesized. In the first step, the olefinic group is epoxidized, and subsequently, the functional group attacks the ring and opens the epoxide to afford the desired cyclized product, with or without the use of a suitable additive (Schemes and ).…”
Section: 22‐trifluoroacetophenonementioning
confidence: 99%
“…Benzofuransa nd indolines are bicyclic compounds that possess av ery important skeleton for pharmaceuticals, bioactive compounds, and natural products. [102,103] Utilizing o-allylanilines andp henols as starting materials, a variety of indolines, [104] pyrrolidines, [104] and dihydrobenzofurans [105] can be synthesized. In the first step, the olefinic group is epoxidized, and subsequently,t he functional group attacks the ring and opens the epoxide to afford the desired cyclized product, with or without the use of as uitable additive (Schemes 28 and 29).…”
Section: 22-trifluoroacetophenone:a No Rganocatalyst For Alkene Oxmentioning
confidence: 99%
“…We have been interested in developing new, green and sustainable processes for the synthesis of compounds . Along these lines, we had previously introduced organocatalytic oxidation protocols for the synthesis of benzodihydrofurans and indolidines , . Herein, our goal was to introduce a sustainable methodology for the synthesis of the family of indoles and benzofurans.…”
Section: Resultsmentioning
confidence: 99%
“…Research work in recent years has shown that TFAP can be used as a green organocatalyst in synthetic procedures, e.g. for the epoxidation of alkenes (Limnios & Kokotos, 2014a), the oxidation of allyloximes to form isoxazoline (Triandafillidi & Kokotos, 2017), the oxidation of aliphatic tertiary amines and azines (Limnios & Kokotos, 2014b) and for the synthesis of substituted tetra-hydrofurans (Theodorou & Kokotos, 2017a), indolines and pyrrolidines (Theodorou & Kokotos, 2017b), besides being used for the synthesis of fluorinated polymers (Guzmá n-Gutié rrez et al, 2008). Interestingly, TFAP has been also used for probing intermolecular interactions involved in the bi-molecular complexes formed on Pt(111) surfaces (Goubert et al, 2011).…”
Section: Chemical Contextmentioning
confidence: 99%